Application Of Philosophy Education to Develop Critical Thinking in Elementary School Students in Indonesia in Supporting SDGs in The Era Of Society 5.0 - Rifa Ranti Nuraini (Ebiz Prima Nusa, 2025)
This study discusses the application of philosophy education as an innovative strategy to develop critical thinking in elementary school students to support the achievement of Sustainable Development Goals (SDGs) in the Society 5.0 era. Philosophy education provides space for students to think deeply, analyze problems critically, and understand various points of view. This is important in developing critical thinking skills needed to face global challenges in the Society 5.0 era. Through a philosophy-based approach, students are invited to understand not only academic concepts, but also social values such as equality, justice, and sustainability. This study also examines how the integration of philosophy education in the elementary school curriculum can contribute to the achievement of SDGs, especially in terms of improving the quality of education and inclusive and sustainable character building.